Elimination Kinetics of the Tobacco-Specific Biomarker and Lung Carcinogen 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanol - Goniewicz, Maciej L.; Havel, Christopher M.; Peng, Margaret Wilson; Jacob, Peyton; Dempsey, Delia; Yu, Lisa; Zielinska-Danch, Wioleta; Koszowski, Bartosz; Czogala, Jan; Sobczak, Andrzej; Benowitz, Neal L. (Cancer epidemiology, biomarkers & prevention, 2009)
4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) is tobacco specific and has a longer half-life than other tobacco biomarkers studied thus far. An accurate measurement of the NNAL half-life is important for optimal use to assess exposure to tobacco smoke. We determined the half-life of NNAL in urine in eight daily smokers on a clinical research ward and in five occasional smokers in a real-life environment. Total NNAL in urine was monitored for 14 days in daily smokers after stopping smoking and for up to 60 days in occasional smokers. The average half-life for the terminal phase in the daily smoker group using a two-compartmental body model was 10.3 days (beta phase), and using a noncompartmental model, it was 9.1 days. In the occasional group, these values were 17.6 and 16.0 days, respectively. The alpha-phase half-lives were 14.3 and 27.8 hours for the two groups, respectively. The inter-subject coefficient of variation of the NNAL terminal half-life ranged from 14% to 30%, and the intra-subject coefficient of variation ranged from 3% to 18%. There was very good agreement between the plasma and urinary half-lives in two subjects with plasma analyses: 7.4 versus 7.9 days and 9.2 versus 10.7 days. Mean renal clearance of NNAL was 13 ± 2.3 mL/min. The terminal half-life of NNAL of 10 to 18 days indicates that this biomarker can be used to detect tobacco smoke exposure for 6 to 12 weeks after cessation of exposure and requires a similar time to assess the steady levels of NNAL after switching from one tobacco product to another. (Cancer Epidemiol Biomarkers Prev 2009;18(12):3421–5)